USE OF BACTERIAL GHOSTS AS NOVEL DRUG DELIVERY SYSTEMS TO BOOST CANCER TREATMENT - F, PRO. ABRSIA F; p., DR.GEECASIS (International Journal of Multidisciplinary Research and Studies, 2021)
The bacterial ghost (BG) system represents a completely unique and progressive approach within the development of bacterial-mediated cancer immunotherapy. The empty inner space of BGs are often crammed with drugs, proteins, DNA, enzymes, and other compounds. The induced lysis process doesn’t harm the essential structural components of the bacteria, giving rise to immunologically active particles capable of stimulating the host system and delivering specific antigen (Ag) to professional antigen-presenting cells (APCs) or active substances to the target cells. Production of bacterial ghosts: BGs are produced by expression of cloned gene E from bacteriophage ϕX174 leading to cell lysis in Gram-negative bacteria, like E. coli K12 strains, Klebsiella pneumonia, Mannheimia (Pasteurella) haemolytica, Neisseria meningitides, Salmonella typhimurium, Vibrio cholera, Helicobacter pylori, and others. Expression of gene E may be placed under transcriptional control of either the thermosensitive EpL/pR-cI857 promoter or chemical inducible promoter repressor systems, like lacPO or the tol expression system. Gene E codes for 91 amino acids and exerts its lytic function by fusion of the inner and outer cell membranes, forming a particular transmembrane tunnel structure through which all the cytoplasmic content is expelled, thus leaving a bacterial envelope called a BG void of nucleic acids, ribosomes, and other intracellular constituents. The inner membrane (IM) and outer membrane (OM) structures of BGs remain intact during the lysis process. microscopy studies and enzymatic studies clearly showed a sealed periplasmic space at the border of the lysis tunnel. The efficiency of the E-mediated lysis process, and quantification of generated BGs and non lysed viable bacteria are determined by flow cytometry assays employing a specific dye that’s sensitive to the changes of discriminatory power of membrane potential and stains only cells that have lost membrane potential (BGs or dead bacteria). Bacterial ghosts as advanced drug delivery systems: Many diseases including cancers require the systemic administration of highly aggressive drugs to already immunocompromised patients. Deleterious and sometimes severe side effects result from a scarcity of cellular and tissue selectivity. Another major issue is that the poor solubility of some drugs employed in cancer treatment. Considering these limitations, the event of a safer and more efficient drug delivery system (DDS) is that the priority for future advanced cancer treatments. Recently, bacterial ghosts made up of the colonic commensal Mannheimia haemolytica were used for in vitro delivery of doxorubicin (DOX) to human colorectal adenocarcinoma (Caco-2) cells. Adherence studies showed that the M. haemolytica ghosts targeted the Caco-2 cells and released the loaded DOX within the cells. Cytotoxicity assays showed a two-fold enhancement in cytotoxic and anti-proliferative activity in cells incubated with DOX-loaded ghosts compared with cells that DOX was directly added to the culture media. This phenomenon could be caused by the degradation of DOX-loaded BGs within the endo-lysosome of target cells allowing DOX to bypass the multi-drug resistance (MDR) efflux pumps and leading to enhanced accumulation of DOX within the cytoplasm and so within the nuclear area of target cells. Current work with bacterial ghosts lies within the investigation of the carrying capacity of the cytoplasmic lumen. This intracellular space of BGs may be filled either with water-soluble substances or emulsions such the drug(s) of interest will be coupled to streptavidin anchored on the within of the cytoplasmic membrane. Moreover, bacterial ghosts may be filled and sealed for the delivery of fluid, non-anchored substances. during a recent study, E. coli ghosts were crammed with the reporter substance calcein and were sealed by fusion with membrane vesicles to take care of inner membrane integrity. Adherence and uptake studies showed that murine macrophages and human Caco-2 cells took up the bacterial ghosts, and calcein was released within the cells. Bacterial ghosts as immunologically active particles: due to the unique structure of the BG’s envelope with preserved pathogen-associated molecular patterns (PAMPs), BGs are often utilized in biomedicine alone as an adjuvant or as a delivery vehicle for drugs or genes. The inner space of BG’s empty envelope will be loaded with a mixture of peptides, drugs, or foreign DNA which allows us to style new sorts of polyvalent vaccines. BGs have excellent DNA loading capacity varying from 4000 to 6000 plasmid copies per BG betting on the concentrations of DNA solution used. BGs loaded with plasmid DNA are efficiently internalized and phagocytosed by both professional APCs and tumor cells. Cross-presentation of Ag delivered to dendritic cells (DCs) by BGs can activate both CD4+ and CD8+ T cells and stimulates the system to reinforce the response against Ag expressed by target cells. Inner and outer membrane structures of BGs including lipopolysaccharide (LPS) and other PAMPs remain intact after protein E-mediated lysis of Gram-negative bacteria. Thus, besides possessing a high loading capacity; BGs carry highly effective molecules for the stimulation of cross-presentation by DCs on their surface, especially, tumor-associated antigens (TAAs). BGs with their intact envelope structures don’t seem to be only immune-stimulatory to professional phagocytes but also are capable of providing stimulatory signals to tumor cells. it’s known that melanoma cells have the capacity to behave as non-professional APCs and may phagocyte both apoptotic and live cells, and it absolutely was recently shown that melanoma cells actively reply to exposure to BGs by increasing their rate of phagocytosis. Using BGs for gene delivery to the immune-competent cells, specifically, DCs yet as tumor cells could initiate or restore the immunologic response against the delivered TAAs moreover as induce and increase the expression of target genes by APCs and tumor cells.